Restoring metabolic flexibility: targeting organelle interaction networks in the pathogenesis and therapy of MASLD - Liu, Yiming; Wang, Yue; Zhou, Jiaying; Li, Hong; Liu, Caiyun; Zhong, Beilei; Liu, Juan; Liu, Leiming; Zhang, Lingling; Sun, Leimin (Frontiers in Cell and Developmental Biology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a complex and heterogeneous metabolic disorder where subcellular organelle dysfunction and disrupted inter-organelle communication are recognized as increasingly important drivers of pathogenesis, moving beyond traditional views focused solely on macroscopic metabolic regulation. This review systematically explores the functional impairments of key organelles—including mitochondria, the endoplasmic reticulum, lipid droplets, and autophagic pathways—to delineate their collective roles in fostering lipid metabolism imbalance, oxidative stress, and inflammation. A key innovation discussed is how the pathological dysregulation of membrane contact sites (MCSs) acts as a pivotal mechanism decoupling organelle function and accelerating disease progression. We conclude that therapeutic strategies aimed at restoring cellular metabolic flexibility—by precisely modulating MCSs, activating clearance pathways, and restoring energy metabolism—represent a promising new paradigm for treating MASLD, particularly in patient populations unresponsive to current therapies.